Forensic Analysis of Popular Social Media Applications on Android Smartphones - Eriş, Fatma Güneş; Akbal, Erhan (My University, 2021)
The use of mobile devices as an evidence of crime has increased. Social network forensics is a branch of science that includes accessing and analyzing many personal data that may contain evidence on social networks. Considering the multiplicity of personal data artefact by social networking applications in mobile devices, the importance of examining social media applications in mobile devices emerges. In this study, the necessary processes for the forensic investigation of mobile devices are examined, the necessary procedures for data extraction from mobile devices are explained and it is revealed how the analysis of social media applications in terms of forensic information in mobile devices should be realized. In the application part of the study, the most widely used mobile operating systems on android devices with android operating prompts; Facebook, WhatsApp Messenger, Instagram, Twitter applications have been installed, basic user behavior analysis of devices that have been performed. During the investigation phase, Oxygen Forensic, Paraben E3: DS and Magnet Axiom were used as tools for manual data extraction and mobile forensic information. The obtained data by both methods are shown comparatively.
Keywords: Mobile Forensics; Social Media Applications; Android OS; Instant messaging